2015
DOI: 10.1038/sj.bdj.2015.591
|View full text |Cite
|
Sign up to set email alerts
|

Are e-cigarettes a gateway to smoking or a pathway to quitting?

Abstract: Over recent years there has been a massive increase in the usage of electronic cigarettes (e-cigs) by the general public. There are mixed views regarding the safety and efficacy of e-cigs, even among healthcare professionals. While some individuals view e-cigs as a public health concern, others recommend them as a safe alternative to conventional cigarettes for smokers who are willing to quit. Since e-cigs are a new phenomena, many clinicians are unaware of their impact on users (known as vapers), who may seek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…8,48,9198 Two conducted a bibliometric review of the ENDS literature 86,99 and 46% of the reviews were systematic. 11,13,15,16,2228,33,34,36,39,46,48,5358,60,61,66,68,7075,7982,85,86,8890,93,97,100104 The dramatically changing product landscape warrants frequent updates and synthesis of the rapidly growing evidence to inform prudent practice, policy, and regulation. 9,105,106 This comprehensive review presents a current synthesis of empirical studies on ENDS across a broad range of topics.…”
Section: Contextmentioning
confidence: 99%
“…8,48,9198 Two conducted a bibliometric review of the ENDS literature 86,99 and 46% of the reviews were systematic. 11,13,15,16,2228,33,34,36,39,46,48,5358,60,61,66,68,7075,7982,85,86,8890,93,97,100104 The dramatically changing product landscape warrants frequent updates and synthesis of the rapidly growing evidence to inform prudent practice, policy, and regulation. 9,105,106 This comprehensive review presents a current synthesis of empirical studies on ENDS across a broad range of topics.…”
Section: Contextmentioning
confidence: 99%
“…Attention has repeatedly been drawn to the fear that ecigarettes might act as a gateway to smoking or a means of renormalising smoking (Alwasi, Nour, & Prabhu, 2015;Barrington-Trimis, Behane, & Unger, 2016;Leventhal et al, 2015;McKee, Chapman, Daube, & Glantz, 2014). The fear that e-cigarettes might act as a smoking gateway have been driven in part by research in the U.S. which has shown that young people reporting past e-cigarette use are more likely (on follow-up) to report having smoked combustible cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…‘candy’ flavour), and via social media 19 . Although many jurisdictions where ENDS can be legally purchased have bans on sales to minors when the e‐liquid contains nicotine, 20–22 ENDS are often easily obtained through informal social sources, such as friends and family members 23 . Further, few countries enforce age restrictions on the purchase of e‐liquids that do not contain nicotine 22 .…”
mentioning
confidence: 99%
“…Although many jurisdictions where ENDS can be legally purchased have bans on sales to minors when the e‐liquid contains nicotine, 20–22 ENDS are often easily obtained through informal social sources, such as friends and family members 23 . Further, few countries enforce age restrictions on the purchase of e‐liquids that do not contain nicotine 22 . Recent meta‐analyses of youth cohort studies published by the WHO 24 and others 69 suggest that use of ENDS by non‐smoking young people can as much as quadruple the odds of later tobacco use 25 .…”
mentioning
confidence: 99%